ANALISIS VALUE CHAIN DALAM UPAYA PENINGKATAN COMPETITIVE ADVANTAGE - Ratna Christiana Dewi (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2017)
Introduction: This study aims to identify primary activities in the value chain analysis process to increase competitive advantage (competitive advantage) in order to support the cost leadership strategy of East Java Youth Lodging in order to survive and win with other tourist lodges and inns in Surabaya.Methods: This research uses a qualitative approach with the method chosen is a case study, while the type of this research is exploratory research.Results: The result of this research is that East Java Youth Lodging still has the opportunity to develop and compete in facing business threats because the Youth Lodging currently has a cost leadership strategy. East Java Youth Lodging as one of the accommodation services that offers cheaper prices with services and facilities that are no less than tourist lodges and other inns in Surabaya.Conclusion: Through the indication of primary activities with the value chain analysis process identified cost drivers that create opportunities for cost reduction, especially in logistics, so that the reduction in costs can be used as an increase in competitive advantage for East Java Youth Lodging.